Field‐Aligned Current Structures During the Terrestrial Magnetosphere's Transformation Into Alfvén Wings and Recovery - J. M. H. Beedle; L.‐J. Chen; J. R. Shuster; H. Gurram; D. J. Gershman; Y. Chen; R. C. Rice; B. L. Burkholder; A. S. Ardakani; K. J. Genestreti; R. B. Torbert (Geophysical Research Letters)
Abstract On 24 April 2023, a Coronal Mass Ejection event caused the solar wind to become sub‐Alfvénic, leading to the development of an Alfvén Wing configuration in the Earth's magnetosphere. Alfvén Wings have previously been observed as cavities of low flow around moons in Jupiter's and Saturn's magnetospheres, but the observing spacecraft did not have the ability to directly measure the Alfvén Wings' current structures. Through in situ measurements made by the Magnetospheric Multiscale spacecraft, the 24 April event provides us with the first direct measurements of current structures during an Alfvén Wing configuration. These structures are observed to be significantly more anti‐field‐aligned and electron‐driven than the typical diamagnetic magnetopause current, indicating the disruption caused to the magnetosphere current system by the Alfvén Wing formation. The magnetopause current is then observed to recover more of its typical, perpendicular structure during the magnetosphere's recovery from the Alfvén Wing formation.